Infection of Prosthetic Vascular Grafts - أحمد, غانم (Latakia University Journal -Medical Sciences Series, 2020)
Introduction: Prosthetic graft infection is a major complication of vascular surgery associated with high morbid-mortality rates. This retrospective single center study evaluated our experience in the management of prosthetic vascular graft infections. Methods: We reviewed the clinical files of patients who had vascular grafts implanted at our department between January 2017 and January 2020 and analysed the cases that developed Samson. group 3, 4 and 5 infections until 1\1\2020. Results: From January 2017 to January 2020, 6 consecutive patients (4 males, 2 females) with median age 63 years were admitted to our department with the diagnosis of vascular graft. Infection accounting for an incidence of 4%. 50% of these infections were early infections. 50% of infections were due to infection of a femoro-popliteal bypass. Using Samson classification, 50% were group 5, 33,33% were group 4 infections and 16,66% were group 3 infection. We performed graft preservation in one patient, graft excision without revascularization in 2 patients; Excision + insitu replacement in 2 patients; Excision + Extra-anatomic bypass in one patient. Our amputation rate was 33,33% and our related death rate was 16,66%. Conclusions: Our amputation and mortality rates are according the published reviews. Each situation needs to be individualized as there is no consensus nor guiding algorithms about what should be the best medical treatment.